Kajian E-Business terhadap Pengambilan Keputusan dalam Kewirausahaan Bisnis Digital - Devi Wardiyanti; Ketut Sumardana; Sussanti Sussanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research is a literature study that makes digital business a part of e-business, which has a significant impact on the progress of the business world today. The emergence of online buying and selling transactions makes it possible for products to be accessed, prices to be known, and negotiations to be carried out without the need to attend the sales location in person. Implementing e-business in a particular business unit can bring advantages or disadvantages to that business unit. However, if analyzed further, the positive benefits of e-business tend to outweigh the negative effects. Surveys show that businesses that use the internet as a promotional medium experience greater sales increases compared to conventional business models. Digital business marketplaces enable thousands of suppliers and millions of buyers to interact with each other, ensuring they can obtain products that suit their needs. This proves that digital business has become an important sector that supports entrepreneurship, with a model that is more flexible and easily accessible to various consumer segments wherever they are.